The Wiley Blackwell handbook of forensic neuroscience - Beech, Anthony R.; Carter, Adam J., 1968-; Mann, Ruth E., 1965-; Rotshtein, Pia (John Wiley & Sons, 2018)
The Wiley Blackwell handbook of forensic neuroscience offers in-depth and enlightening coverage of the neurobiology of sex and sexual attraction, aggressive behavior, and emotion regulation; the neurobiological bases to risk factors for offending such as genetics, developmental, alcohol and drugs, and mental disorders; and the neurobiology of offending, including psychopathy, antisocial personality disorders, and violent and sexual offending.